DAMPAK PEMBELAJARAN JARAK JAUH (PJJ) DI PERGURUAN TINGGI PADA MASA WABAH PANDEMI COVID-19 TERHADAP PEMAHAMAN MATERI MAHASISWA (Studi Eksploratif Mahasiswa Sarjana PAI IAIN Salatiga) - abdul khamid; Muchamad Chairul Umam (Universitas Wahid Hasyim Semarang, 2021)
This study aims to determine how the strategies carried out during distance learning (PJJ) during the Covid-19 pandemic outbreak of PAI IAIN Salatiga undergraduate students. Then the impact of the advantages or positives from the implementation of distance learning (PJJ), as well as the inhibiting factors. This research uses a qualitative approach. Primary data were collected using google form and secondary data from articles or journals, books and literature related to this research. From this research, it is known that the strategy for implementing distance learning (PJJ) in Salatiga is to take advantage of technological developments such as: zoom meetings, whatsapp groups, google forms, google classroom, google meet, and youtube. As for the positive or supporting impacts, namely: a) knowing the various applications and developments in science and technology, b) anticipating the rate of spread of the Covid-19 virus outbreak, c) PJJ is more lenient in time without requiring to come to the campus, it is enough to learn from their respective homes, d) material well and can spend more time with family. While the inhibiting effects are: a) lack of understanding in understanding the material, b) lack of maximal in lectures due to signal constraints, c) lack of interaction from student to lecturer or student to other students, d) most of them give assignments without the delivery of material first.